Innovations for sustainable biomass utilisation in the Upper Rhine Region - Schumacher, Kira [Hrsg.]Fichtner, Wolf [Hrsg.]Schultmann, Frank [Hrsg.] (Produktion und Energie / Karlsruher Institut für Technologie, Institut für Industriebetriebslehre und industrielle Produktion u. Deutsch-Französisches Institut für Umweltforschung, 2017)
This book provides insight into the project 'OUI Biomasse' by summarising selected results. The major goal was the development of a knowledge-based sustainable biomass strategy for the transition of the energy system of the Upper Rhine Region. The 'OUI Biomasse' network studied all aspects of the biomass value chain to come up with development scenarios, analyse their potential impact in terms of sustainability criteria and to draft guidelines for the sustainable use of biomass.